Government Gardens, Trinidad - (:unkn) unknown (My University, 2010)
The Government Garden originally known as the Royal Botanic Gardens, lies to the north of the Queen's Park Savannah. The Gardens, which carry a variety of local and foreign trees and plants, were designed under the direction of the Governor, Sir Ralph Woodford. Postcard number 60716.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Gardens--Trinidad and Tobago; Palms--Trinidad and Tobago